Iterative learning control for electrical stimulation and stroke rehabilitation. (2015) - (College teacher), Freeman, Chris T; (Professor), Rogers, Eric; Burridge, Jane H; Hughes, Ann-Marie; Meadmore, Katie L
No abstract available